Structure relocation - Drozd, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Civil engineering is constantly changing and introducing new technologies of building, demolishing, restructuring, modernisation, etc. The article presents the innovative subject of relocation of structures, i.e. moving them to a different place. The difficulty of relocation is influenced by the technical condition of the structure, its weight, and intended time duration of the relocation. The article shows how complex discussed issue is. The subject was selected due to its infinitesimal presence in the literature.
Keywords: civil engineering; new technologies of building; relocation of structures; demolishing; modernisation; structures; inżynieria lądowa; nowe technologie budowlane; przenoszenie konstrukcji; wyburzanie; modernizacja